Effect of Muslin Bagging Technique on the Control of Greater Date Moth:ArenipseSebella(Hamps)Lepidoptera:Pyralidae and Lesser Date Moth Batrachedra amydraula (Meyr) Lepidoptera :Mumphidaon On Data palm of Missan - Kazim, Salih (University of Thi-Qar Journal of Science, 2012)
This study was conducted to combat Arenipses Sebella and Batrachedra amydraula by coveringbunch palm. The experiment started in March 2009 and 2010 in the gardens of the Aldfas within the Missan province. The experiment was conducted by using five treatments. The first treatment Spray bunch palm nets Pyrethrum and the spray rate of every two months and that in March and may and July and September. the second treatment are spraying pesticide coverage with the lifting of the cover recurring bunch nets sprayed with Pyrethrum mints in march and then covered with bags muslin directly for a period of 60 days and reiterated the steps the same transaction in June.the third treatment is to cover bunch bags beginning of march until the harvest of fruits and fourth treatment is spraying pesticide in question.coverge immediately until the harvest of fruits either fifth treatment of control.Results showed that the lowest infestation and intensity percentage of the fruits by two lepidopterist insects. Greater and lesser date moths were in the fourth treatment, then in the third one. On the other hand infestation and intensity percentage were not significantly different from control first and the second treatment .in addition the weights of fruit at harvest under the influence of those transaction, the result showed superiority treatment and then the fourth treatment, while the third .was the lower weight is the treatment of the fifth and the first and second. Bags injury also prevented other fruit pests such as insect stores and birds